Validity and reliability of the Quality of Life in Reflux and Dyspepsia (QoLRAD) questionnaire in patients with gastroesophageal reflux disease for the Turkish population - Hançerlioğlu, Sadık; Yıldırım, Yasemin; Bor, Serhat (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: Gastroesophageal reflux disease negatively affects quality of life. The aim is to improve quality of life because of high recurrence rate. There is a strong need for patient-reported outcome measures. The present study aimed to evaluate the validity and reliability of the Quality of Life in Reflux and Dyspepsia Questionnaire (QoLRAD) to adopt it into Turkish. Materials and Methods: A total of 142 patients with complaints of heartburn or regurgitation once a week or commonly diagnosed with 24-hour intraesophageal impedance-pH monitoring and/or upper gastrointestinal endoscopy were included in this study. Sociodemographic Data Collection Form, QoLRAD-TR, and Short Form-36 (SF-36) were applied to patients who were off proton pump inhibitors. Results: The Cronbach’s alpha coefficient value of the questionnaire was 0.97, and the intraclass correlation coefficient (ICC) value of the result of test-retest method was between 0.97 (Vitality) and 0.99 (Eating/Drinking Disorders). There was a positive correlation between all subdomains of QoLRAD-TR and SF-36 scales. The lowest correlation (0.10) was between Emotional Distress and Role-emotional Limitations, and the highest (0.34) was between Energy and Vitality. Conclusion: The QoLRAD test measuring quality of life, except some subdomains in our study that we performed on patients diagnosed with GERD, was found to be valid and reliable. Cite this article as: Hançerlioğlu S, Yıldırım Y, Bor S. Validity and reliability of the Quality of Life in Reflux and Dyspepsia (QoLRAD) questionnaire in patients with gastroesophageal reflux disease for the Turkish population. Turk J Gastroenterol 2019; 30(6): 511-6.